Search for continuous gravitational waves from neutron stars in globular cluster NGC 6544 - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Amer Physical Soc, 2017)
We describe a directed search for continuous gravitational waves in data from the sixth initial LIGO science run. The target was the nearby globular cluster NGC 6544 at a distance of approximate to 2.7 kpc. The search covered a broad band of frequencies along with first and second frequency derivatives for a fixed sky position. The search coherently integrated data from the two LIGO interferometers over a time span of 9.2 days using the matched-filtering F-statistic. We found no gravitational-wave signals and set 95% confidence upper limits as stringent as 6.0 x 10(-25) on intrinsic strain and 8.5 x 10(-6) on fiducial ellipticity. These values beat the indirect limits from energy conservation for stars with characteristic spindown ages older than 300 years and are within the range of theoretical predictions for possible neutron-star ellipticities. An important feature of this search was use of a barycentric resampling algorithm which substantially reduced computational cost; this method is used extensively in searches of Advanced LIGO and Virgo detector data.